Profesionalisme Kepemimpinan dalam Manajemen Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
Leadership professionalism has become one of the determining factors in the success of Islamic education management, particularly in responding to the complexity of social changes, technological developments, and the increasing demands for institutional quality improvement. This study aims to analyze the concept of leadership professionalism from the perspective of Islamic education management and to identify the strategic role of leaders in establishing effective, adaptive, and sustainable educational governance. This study employs a qualitative research method with a literature review approach (library research) through an analysis of various academic sources, including journal articles, scholarly books, and relevant research publications related to educational leadership, leadership professionalism, and Islamic education management. Data analysis was conducted using content analysis techniques through the stages of identification, categorization, interpretation, and synthesis of various theoretical perspectives. The findings reveal that leadership professionalism in Islamic education management is constructed through three main dimensions: the leader’s capacity to develop quality-oriented educational governance, the integration of managerial competencies with Islamic spiritual values, and transformational abilities in directing institutional change. Islamic education leaders do not merely function as organizational administrators but also serve as agents of change who are capable of developing a quality culture, enhancing human resource capacity, and maintaining a balance between the demands of educational modernization and Islamic identity. This study emphasizes that strengthening leadership professionalism is a fundamental strategy for improving the effectiveness of Islamic education management and creating educational institutions that are innovative, adaptive, and competitive.